Enhancement of retinal Müller glia’s phagocytic activity against hard exudates by conbercept via activation of PPARγ-CD36 axis in diabetic retinopathy - Ying-Ying Zhu; Shi-Yue Qin; Hai Xie; Yin-Ping Liu; Xiao-Sa Li; Chao-Yang Zhang; Yan-Chun Zhang; Jing-Fa Zhang (International Journal of Ophthalmology)
AIM: To investigate the effects and the underlying mechanism(s) of conbercept on the phagocytosis of hard exudates (HEs) by Müller glia in diabetic retinopathy (DR). METHODS: Twenty-one eyes from 17 patients with diabetic macular edema (DME) underwent optical coherence tomography (OCT) imaging to examine the changes of HEs before and after intravitreal conbercept injection (IVC). In vitro, rat retinal Müller cell line (rMC-1) was cultured under high glucose and treated with oxidized low-density lipoprotein (Ox-LDL) with or without conbercept. Phagocytosis was analysed with immunofluorescence, flow cytometry, and Western blot. Expressions of scavenger receptors (LOX-1, CD36) were analyzed by quantitative real-time polymerase chain reaction (qRT-PCR). Conbercept's effects on vascular endothelial growth factor A (VEGF-A), VEGFR2, inflammation (NF-κB, IL-6, iNOS), and oxidative stress (ROS) were evaluated with Western blot and immunofluorescence. RESULTS: The area of HEs showed minimal change after the first IVC (1.39±1.41 to 1.38±1.3 mm2, P=0.938), but significantly decreased after the third IVC (0.45±0.66 mm2, P=0.002). In vitro, conbercept enhanced the phagocytosis of Ox-LDL by rMC-1 cells under high glucose condition. Conbercept reduced ROS and inflammation (NF-κB, IL-6, iNOS) in high glucose-treated rMC-1 cells by suppression of VEGF/VEGFR2 pathway. The inhibition of NF-κB by conbercept further activated PPARγ-CD36 axis, increasing CD36 expression and promoting Ox-LDL uptake, thereby facilitating the clearance of HEs. CONCLUSION: Conbercept reduces HEs in DR by enhancing Müller glia phagocytosis possibly through activating PPARγ-CD36 axis, which is mediated by inhibition of VEGF signaling. Modulation of Müller glia phagocytic capacity might provide a novel therapeutic strategy to treat DR and DME.